Organizational Effectiveness Reputation in the Nonprofit Sector. Issue 2 (2nd April 2016) - Willems, Jurgen; Jegers, Marc; Faulk, Lewis
ABSTRACT: Public organizations are increasingly relying on nonprofit partners for the delivery of public services, a trend that makes performance assessments of nonprofit organizations important for the allocation of government resources. However, nonprofits engage multiple stakeholders, and this leads to complex sets of organizational goals and highly subjective assessments of nonprofit effectiveness. We develop a literature-based model to understand the subjective assessments of organizational performance by stakeholders that taken together constitute an organization's effectiveness reputation. In this model, effectiveness reputation is impacted by stakeholder trust and satisfaction, which are in turn impacted by output ambiguity and stakeholder involvement. We find support for our model with a structural equation modeling (SEM) analysis based on survey data of organizational stakeholders (n = 284). We propose further research steps and highlight practical implications for nonprofit managers and public administrators.